PENGARUH METODE EDUTAINMENT DAN IDENTITAS DIRI TERHADAP KETERAMPILAN SOSIAL ANAK - Nesna Agustriana (IAIN Bengkulu, 2018)
This study aimed to determine the effect of method of edutainment and self-concept towards the children's social skills in group A. The research method used in this research is experimental method with the treatment design by level 2 x 2 with 48 children samples. Social skills research data obtained was analyzed by analysis of variance (ANOVA) two lines and, which firstly tested by requirements test analysis through normality test with Liliefors test and homogeneity test with Bartlett test. The results showed that, (1) there are differences in social skills children treated edutainment method to approach the game with the children who were given treatment methods edutainment multimedia approach, (2) there are significant interaction between method of edutainment and self-concept of the child's social skills, (3) there are differences in social skills children treated edutainment method to approach the game with the children who were given treatment methods edutainment multimedia approach to children who have a positive self-concept, (4) there are differences in social skills children treated edutainment method to approach the game with the children who were given treatment methods edutainment multimedia approach to children who have a negative self-concept. Keyword : Edutainment Methode, Social Skill, self-identity